Assessment of vitamin D levels in newly diagnosed children with type 1 diabetes mellitus comparing two methods of measurement: a facility's experience in the Middle Eastern country of Bahrain - Al-Haddad FA (Dove Medical Press, 2016)
Fatima Ahmed Al-Haddad,1 Mansoor H Rajab,2 S Mahmood Al-Qallaf,3 Abdulrahman O Musaiger,4 Kathryn H Hart5 1Dietetic Unit for Hospitals, 2Pediatric Endocrine and Diabetes Team, Pediatric Department, Salmaniya Medical Complex, 3Pharmacy Program, College of Health Sciences, University of Bahrain, Manama, 4Nutrition and Health Studies Unit Deanship of Scientific Research, University of Bahrain, Sakheer, Kingdom of Bahrain; 5School of Biosciences and Medicine, Department of Nutritional Sciences, University of Surrey, Guildford, UK Background: The number of children being diagnosed with type 1 diabetes mellitus (T1DM) is on the rise and has more than doubled in the past 10 years in Bahrain. Some studies have linked low vitamin D levels with an increased risk of diabetes. There are concerns regarding the variations in circulating 25(OH)D levels measured by different laboratories and by using different analytical techniques. Objective: The aim of this study was to evaluate the vitamin D levels of newly diagnosed children with T1DM using the “gold standard method” with high-pressure liquid chromatography–tandem mass spectrometry methods compared to the chemiluminescence micro-particle immunoassay (CMIA) used in a hospital laboratory. Subjects: Eighteen children, aged 6–12 years, who received a confirmed diagnosis of T1DM in 2014 were chosen as subjects. Methods: Serum vitamin D levels were assessed in a hospital, while an extra aliquot of blood collected during routine blood collection after acquiring informed written consents from the subjects, and sent to Princess Al-Jawhara Center for Molecular Medicine and Inherited Disorders to be analyzed by ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS). Results: The mean age of the study group was 9±2 years. The mean total of 25(OH)D levels (D3 and D2) assessed by UPLC-MS/MS was 49.7±18.8, whereas the mean total of 25(OH)D levels obtained from the CMIA assay was 44.60±13.20. The difference in classification between the two methods was found to be statistically significant (P=0.004). A Bland–Altman plot showed a poor level of agreement between the two assay methods. The CMIA overestimated insufficient values and underestimated deficiency, when compared to UPLC-MS/MS. Conclusion: There was a statistically significant difference between the two assay methods with CMIA overestimating vitamin D insufficiency. Clinicians should be prudent in their assessment of a single vitamin D reading, when the gold standard method is not available or feasible. Keywords: type 1 diabetes, children, vitamin D, Middle East